INTEGRATED PUBLIC SECURITY SERVICE CENTERS IN MATO GROSSO DO SUL: A PROPOSAL FOR SERVITIZATION - Mascaro , Rafael; Ovando, Rômulo Gustavo de Moraes (Seven Editora, 2024)
The work proposes an analysis of the concept of servitization and its application in the public sector, specifically in the area of public security. The objective is to demonstrate the potential benefits of the implementation of Integrated Public Security Service Centers in Mato Grosso do Sul, applying the concept of servitization and the philosophy of Community Policing. The research uses a qualitative approach and describes the attributions of public security agencies in the State, presents a theoretical foundation on Community Police and servitization, and exposes examples of integrated service in public security in other states of Brazil and in Mato Grosso do Sul itself. The expected result is the proposal to implement a new model of public security service provision in the State. DOI:https://doi.org/10.56238/sevened2024.031-041